Linguistic foundations of identity : readings in language, literature and contemporary cultures - Prakash, Om (Linguistic teacher); Kumar, Rajesh (Abingdon, Oxon ; New York, NY : Routledge, 2021)
The collection of chapters in this book brings together researchers working in paradoxes and complexities of cultural identities through uses of language and literature from varied perspectives. This volume is an important step towards achieving the goal of reaching out to many who have been looking at the complexities of identity formation from linguistic, cultural, social and political perspectives.Please note: This title is co-published with Aakar Books, New Delhi. Taylor & Francis does not sell or distribute the Hardback in India, Pakistan, Nepal, Bhutan, Bangladesh, Maldives and Sri Lanka.
26. Language as Real as Magic Realism: Many worlds and beyond in One Hundred Years of Solitude -- 27. Instrumentality of Language: How Dravidian Politicians Use Language -- About the Editors -- About the Contributors -- Praise for the Book
OCLC-licensed vendor bibliographic record.
Keywords: Sociolinguistics -- India; Language and culture